Outcome of Ischemic Heart Disease in the Intensive Care Unit in a Tertiary Care Hospital - Poonam V Sancheti; Suresh K Mangulikar (Medsci Publications, 2017)
Introduction: Non communicable diseases are growing causes of mortality developing world. Objectives of the study were to studythe socio-demographic profile of ischemic heart disease cases in ICU in the tertiary care hospital and to study the outcome of ischemic heart disease cases in ICU in the tertiary care hospital. Methods: It was a hospital based descriptive study. Study was carried out in patients of IHD admitted in ICU of tertiary care hospital. The patients were informed about the examination. History was obtained from patients or relatives. Outcome was recorded. Appropriate Statistical analysis was used. Results: Occurrence of disease was increasing as age advances. 66.92% patients were from urban and 33.08% were from rural areas. Maximum patients 72.77% were discharged after symptomatic relief. Highest deaths were in 70 years and above. Maximum deaths were noted in patients brought between 12 hours to 1 day. Highest deaths were seen in patients stayed for< 1 day, 84.62%. Conclusions: Age, duration of hospital stay and duration between onset of symptoms and treatment are related to outcome of the patients with IHD. Association between the variables is studied in present study.